2013
DOI: 10.1089/ten.tec.2012.0671
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Humidity and Solution Viscosity on Electrospun Fiber Morphology

Abstract: Electrospinning is a popular technique to fabricate tissue engineering scaffolds due to the exceptional tunability of fiber morphology that can be used to control scaffold mechanical properties, degradation rate, and cell behavior. Although the effects of modulating processing or solution parameters on fiber morphology have been extensively studied, there remains limited understanding of the impact of environmental parameters such as humidity. To address this gap, three polymers (poly(ethylene glycol) [PEG], p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
210
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(236 citation statements)
references
References 71 publications
13
210
1
Order By: Relevance
“…The choice of polymer solution (fibrin or fibrin-PLGA) as well as the ambient parameters temperature and humidity are important factors that affect the spinning quality [Nezarati, 2013].…”
Section: Electrospun Fibrin-plga Fibers and Formation Of A Tubular Stmentioning
confidence: 99%
“…The choice of polymer solution (fibrin or fibrin-PLGA) as well as the ambient parameters temperature and humidity are important factors that affect the spinning quality [Nezarati, 2013].…”
Section: Electrospun Fibrin-plga Fibers and Formation Of A Tubular Stmentioning
confidence: 99%
“…In the case of electrospinning poly-carbonate urethane, fibre collection dropped at high humidity, most likely due to increased electrostatic discharge. In the same study, humidity below 50% resulted in fibre breakage due to decreased electrostatic discharge from the jet for all three polymers that were electrospun (Polyethylene glycol, poly carbonate urethane and polycaprolactone) [13,15,16]. Tripatanasuwan et al concluded that there is a linear decrease of the diameter of PEO fibres with increasing humidity.…”
Section: Introductionmentioning
confidence: 88%
“…Even if in all the solutions studied, the general trend of the way the relative humidity affects the process was the same, there are discrepancies regarding the thresholds and quantitative results which they attributed to different polymer characteristics [14]. High humidity has also been reported to cause fibre breakage and loss of poly-ethylene glycol fibre morphology, as a result of increased water absorption [15].…”
Section: Introductionmentioning
confidence: 95%
“…As expected, with increasing concentration of the PCL, the non-fibrous region in the cross-section of the struts was enlarged due to the increased viscosity. Generally, high viscosity (i.e., a high concentration of polymeric solution) can generate greater viscoelastic force, which prevents the whipping/stretching motion, finally inducing larger-diameter electrospun fibers versus a low concentration of polymeric solution [31][32][33]. However, at the high flow rate (1.5 mL/h), the effect of PCL concentration was negligible.…”
Section: Effect Of the Flow Rate And Weight Fraction Of Pcl Solutionmentioning
confidence: 99%